EU's geopolitics towards Russia - Tilea, Oleg; Weinfurter, Jaroslav; Garlick, Jeremy; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis examines how domestic political discourses within five EU member states—Germany, France, Poland, Hungary and Czechia—influence the coherence of the European Union’s collective geopolitical strategy toward Russia. Using critical discourse analysis and a multi-level governance perspective, the study analyses how national political actors construct narratives, frames and counter-frames related to Russia’s actions since the occupation of Crimea in 2014. The comparative findings show that diverging threat perceptions, historical experiences and economic dependencies shape national interpretations of Russia, producing both alignment and friction within EU decision-making. While moments of major external shocks, such as the 2022 full-scale invasion of Ukraine, temporarily strengthened unity, underlying discursive divergences persist. The thesis concludes that EU coherence is not solely institutional but fundamentally discursive: the degree of alignment in national narratives directly affects the Union’s capacity to formulate and sustain a common geopolitical response to Russia.
Vedoucí práce: Jaroslav Weinfurter
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses